PENGUJIAN PENGETAHUAN KONSUMEN TERHADAP BAHAYA KEMASAN PLASTIK - Reniwati Lubis; Herri Trisna Frianto (Politeknik Aceh, 2017)
Plastic packaging is often used by consumers or wide community to save food or other objects. Plastic packaging will be dangerous for users if it is not used in accordance with the rules. The purpose of this study was to explain how much the consumer's knowledge of the dangers of plastic packaging so that the consumer(s) or the user(s) couldpreventfrom this risk. This study test was done by using 70 samples around Medan. Meanwhile, it used two variables which were the dependent variable and the free variable. The independent variable was the consumer’s knowledge and the dependent variable was the danger of plastic packaging. The results of this study showed thatmany consumers have aslight knowledgeaboutthe plastic packaging hazards.From 70 samples distributed there are 96% consumers indicated low knowledge of the plastic packaging hazard. The assessment contributed to the consumers consists of 25 items in which under ten items could be answered correctly, 4% with the good knowledge (two people) and enough knowledge (one person) with 5% significant.